2018
DOI: 10.1111/jpc.1_14241
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐areolar dermatitis neglecta

Abstract: See http://onlinelibrary.wiley.com/doi/10.1111/jpc.2_14241/abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…DN can be secondary to pain, hyperaesthesia or prior trauma 5,10 . The various risk factors associated with the development of DN reported in the English literature (including articles from PubMed and Google Scholar) are mentioned in Table 1 1–6,8–32 …”
Section: Pathogenesismentioning
confidence: 99%
“…DN can be secondary to pain, hyperaesthesia or prior trauma 5,10 . The various risk factors associated with the development of DN reported in the English literature (including articles from PubMed and Google Scholar) are mentioned in Table 1 1–6,8–32 …”
Section: Pathogenesismentioning
confidence: 99%
“…3 There are also reports of DN in patients with psychiatric conditions, including depression and schizophrenia, or related to religious beliefs. 5 DN has been reported at a variety of body sites 3,6,7 and at all ages. 8 It is suggested that DN should be kept in mind in the differential diagnosis of all hyperpigmented localised lesions, especially in those with a background of disability.…”
mentioning
confidence: 99%